Organ-specific expression of genes involved in iron homeostasis in wheat mutant lines with increased grain iron and zinc content - Kenzhebayeva, Saule; Atabayeva, Saule; Sarsu, Fatma; Abekova, Alfiya; Shoinbekova, Sabina; Omirbekova, Nargul; Doktyrbay, Gulina; Beisenova, Aizhan; Shavrukov, Yuri (PeerJ, 2022)
Background Iron deficiency is a well-known nutritional disorder, and the imbalance of trace-elements, specifically iron, is the most common nutrient deficiency of foods across the world, including in Kazakhstan. Wheat has significant nutritional relevance, especially in the provision of iron, however many bread wheat varieties have low iron despite the need for human nourishment. In this study, the expression profiles of wheat homologous genes related to iron homeostasis were investigated. The work resulted in the development of two new M5 mutant lines of spring bread wheat through gamma-irradiation (200 Gy) with higher grain iron and zinc content, lower phytic acid content, and enhanced iron bioavailability compared to the parent variety. Mutant lines were also characterized by higher means of yield associated traits such as grain number per main spike, grain weight per main spike, grain weight per plant, and thousand-grain weight. Methods The homologous genes of bread wheat from several groups were selected for gene expression studies exploring the tight control of iron uptake, translocation rate and accumulation in leaves and roots, and comprised the following: (1) S-adenosylmethionine synthase (SAMS), nicotianamine synthase (NAS1), nicotianamine aminotransferase (NAAT), deoxymugineic acid synthetase (DMAS), involved in the synthesis and release of phytosiderophores; (2) transcription factor basic helix-loop-helix (bHLH); (3) transporters of mugineic acid (TOM), involved in long-distance iron transport; (4) yellow stripe-like (YSlA), and the vacuolar transporter (VIT2), involved in intracellular iron transport and storage; and lastly (5) natural resistance-associated macrophage protein (NRAMP) and ferritin (Fer1A). Results The wheat homologous genes TaSAMS, TaNAS1, and TaDMAS, were significantly up-regulated in the roots of both mutant lines by 2.1–4.7-fold compared to the parent variety. The combined over-expression of TaYSlA and TaVIT2 was also revealed in the roots of mutant lines by 1.3–2.7-fold. In one of the mutant lines, genes encoding intracellular iron transport and storage genes TaNRAMP and TaFer1A-D showed significant up-regulation in roots and leaves (by 1.4- and 3.5-fold, respectively). The highest expression was recorded in the transcription factor TabHLH, which was expressed 13.1- and 30.2-fold in the roots of mutant lines. Our research revealed that genotype-dependent and organ-specific gene expression profiles can provide new insights into iron uptake, translocation rate, storage, and regulation in wheat which aid the prioritization of gene targets for iron biofortification and bioavailability.
Keywords: Organ-specific gene expression involved in iron homeostasis; Iron bioavailability and homeostasis; Spring wheat mutant lines; Fe regulation and storage in grains